Beyond Literacy and Motivation: The Overriding Role of Product Innovation in Driving Housewives' Interest in Islamic Gold Savings - Nurun Nazwa Humairoh; Muhammad Iqbal; Rosyada (Journal Of Economic Cluster, 2026)
Despite the accessibility and Sharia compliance of Islamic gold savings, participation among housewives remains suboptimal. This study examines the influence of Islamic financial literacy, investment motivation, and product innovation on the interest in investing in Pegadaian Syariah Gold Savings. Applying a quantitative associative design, the study involved 50 Family Welfare Movement (PKK) members in Srimulya Village, Palembang. Saturated sampling was utilized to include the entire population as respondents. Data collected via Likert-scale questionnaires were analyzed using multiple linear regression. The results reveal that Islamic financial literacy and investment motivation do not significantly affect investment interest. In contrast, product innovation has a positive and significant effect. Simultaneously, the variables explain 73.6% of the variance in investment interest. Theoretically, these findings indicate that mere Sharia knowledge is insufficient to trigger investment intention without perceived behavioral control (ease of use). Managerially, Pegadaian Syariah must prioritize continuous digital product innovation, user-friendly applications, and transparent mechanisms, rather than relying solely on basic financial literacy campaigns, to effectively attract housewives.